2022
DOI: 10.1002/cpt.2642
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Chronic Kidney Disease on the Renal Secretion via Organic Anion Transporters 1/3: Implications for Physiologically‐Based Pharmacokinetic Modeling and Dose Adjustment

Abstract: There is growing evidence that active tubular secretory clearance (CL s ) may not decline proportionally with the glomerular filtration rate (GFR) in chronic kidney disease (CKD), leading to the overestimation of renal clearance (CL r ) when using solely GFR to approximate disease effect on renal elimination. The clinical pharmacokinetic data of 33 renally secreted OAT1/3 substrates were collated to investigate the impact of mild, moderate, and severe CKD on CL r , tubular secretion and protein binding (f u,p … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 45 publications
0
15
0
Order By: Relevance
“…This result suggests that the renal excretion of drugs is reduced due to the functional decline of the entire nephron associated with kidney injury. In addition, active renal transport mediated by organic anion transporter (OAT)-1 and OAT3, which are expressed on the basolateral membrane of the proximal tubular epithelial cells, has been reported to be reduced in patients with CKD (Chapron et al, 2017;Pradhan et al, 2019;Takita et al, 2020;Tan et al, 2022).…”
Section: Renal Pharmacokinetics In Patients With Kidney Diseasementioning
confidence: 99%
“…This result suggests that the renal excretion of drugs is reduced due to the functional decline of the entire nephron associated with kidney injury. In addition, active renal transport mediated by organic anion transporter (OAT)-1 and OAT3, which are expressed on the basolateral membrane of the proximal tubular epithelial cells, has been reported to be reduced in patients with CKD (Chapron et al, 2017;Pradhan et al, 2019;Takita et al, 2020;Tan et al, 2022).…”
Section: Renal Pharmacokinetics In Patients With Kidney Diseasementioning
confidence: 99%
“…[28][29][30] Considering multiple renal elimination mechanisms (glomerular filtration, passive diffusion, and transporter-mediated active secretion), the effect of RI on the function of renal transporters may be convoluted by reduced GFR in patients with RI. Recent PK analysis of 33 drugs that are eliminated substantially by tubular secretion and are substrates of OAT1 or OAT3, suggested that the decrease in unbound tubular secretion clearance exceeds the decline in GFR in patients with severe CKD, 29,31 in contrast to less pronounced change in OCT2. 30,32 Although direct evidence of changes in renal transporter expression/activity in patients with CKD is still lacking, reduced protein expression and activity of several renal uptake transporters was reported in a rat model for chronic kidney failure.…”
Section: Modulation In Transporter Expression and Function In Various...mentioning
confidence: 99%
“…However, the extent of disease‐related modulation differed across transporters and disease severity. For instance, deterioration of OAT1/2/3 activity exceeded changes in GFR in severe CKD, 31 whereas, in the case of OCT2 and MATEs, the estimated decline in transporter activity was suggested to be smaller relative to changes in GFR 30 . Clinical consequences of disease‐related modulation of specific transporter expression/activity will depend on the magnitude of these changes and the contribution of particular transport mechanism(s) to the systemic PK or tissue exposure (see examples in Table 4 ).…”
Section: Pbpk Modeling Of Transporter Substrates In Disease Pregnancy...mentioning
confidence: 99%
“…26 However, recent studies have found opposing evidence that OAT1/3 renal secretion deteriorates at a faster rate compared with GFR, especially in severe CKD. [27][28][29] Several CKD-related effects may be behind this rapid deterioration of OAT1/3 activity, including accumulation of uremic solutes, CKD-related damage to functional proximal tubules, post-translational modifications to serum albumin, decreased albumin levels, and possible decrease in OAT1/3 expression. 28,[30][31][32] Considering relative difficulty in quantitatively measuring OAT1/3 expression in CKD subjects, ability to elucidate changes in OAT1/3 function in CKD with endogenous biomarker-informed PBPK modeling would aid drug dosing of OAT1/3-eliminated drugs in such populations.…”
Section: Articlementioning
confidence: 99%
“…In addition, we recently reported that OAT1/3 CL sec declines beyond the decrease in GFR by an additional 16% in moderate CKD and 50% in severe CKD. 27 These changes were incorporated as an OAT1/3 relative activity factor of 0.84 and 0.50 in the PDA compound file for moderate and severe CKD, respectively (Table 2). Measurement of PDA f u,p was available only for patients with severe CKD.…”
Section: Chronic Kidney Disease Model Applicationmentioning
confidence: 99%